(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2016)
This paper is the result of the research project “Retrospective of natural disasters in Colombia as input for the construction of a decision support system” developed by the Geophysical Institute of the Pontificia Universidad Javeriana and the Catholic University of Colombia. The research goal was to build a decision support system which also incorporates response mechanisms in the territory in the short, medium and long term. Three study cases were taken in the regions of Mojana , Armero and Manatí, where major natural disasters occurred. The preliminary results took the coffee area as a study area focusing on the town of Armero, who suffered the total destruction of its territory by a volcano eruption of Nevado del Ruiz in 1985. The region was characterized together with a fieldwork in order to propose a system of indicators of vulnerability in several dimensions and an action plan in case of a volcano eruption. Also, an application for smartphones was proposed in order to teach how to perform a risk management of a volcanic event.